Factors influencing the development of public secondary school libraries in the third district of Quezon City - Totanes, Vernon R.; Faderon, Rosalie B.; Cruz, Ma. Divina P. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study focused on the factors influencing the development of public secondary school libraries (PSSLs) in the Third District of Quezon City (TDQC). It sought to determine the PSSLs' level of development by using the "Guidelines on the Implementation of School Library Policies and programs" (hereafter referred to as the 1998 Guidelines) -- issued in 1998 by the then Department of Education, Culture and Sports--as a means to come up with a Development Score (DS) for each of the PSSLs, and then identified the factors that influenced the development of the PSSL with the highest DS.
The data gathered were obtained through interviews and ocular inspections with the use of an interview schedule developed from the 1998 Guidelines. None of the librarians interviewed had a copy of the 1998 Guidelines.
The PSSLs, ranked from highest to lowest are : Juan Sumulong High School, Quirino High School, Camp Gen. E. Aguinaldo High School, Carlos P. Garcia High School, Jose P. Laurel Sr. High School, Balara High School, and Don Quintin Paredes Sr. High School. This study then focused on the factors that influenced the development of the Sumulong Library not just because it obtained the highest DS, but also because of the great difference between its DS and the DSs of the other PSSLs. The history of the Sumulong library was reviewed and then factors influencing its development were analyzed.
The presence of LEADERSHIP AND SUPPORT - NOT resources, as many have asserted--was determined to have been the primary factor in the development of the Sumulong library. However, this does not mean that RESOURCES and other factors that influence development are unimportant; instead, LEADERSHIP AND SUPPORT need to be present before any other factors can even be discussed.
Vita.
Thesis (Master of Library and Information Science)
Keywords: School libraries -- Philippines -- Quezon City